Evaluation des paramètres biochimiques de l’effet antidiabétique de la propolis « Etude in vivo chez des rats wistar » - HAMIDI, Chaima; KERROUM, Fayçal (My University, 2023)
Diabetes is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body does not properly use the insulin it produces. Characterized by chronic hyper-glycemia. Today, apitherapy consists in treating with products of the hive. This ancient practice uses the properties of bee products to improve and maintain human health. In this work, we are interested in the study of propolis, a resin with multiple therapies. The objective of this study was to contribute to the evaluation of the in vivo antidiabetic activity of propolis. No effect was shown in all experimental batches after the toxicity test with selected doses of propolis (150 mg/kg, 300 mg/kg, 500 mg/kg). Diabetes was induced in all groups, except for the control group, using streptozotocin (STZ) at a single dose of 60 mg/kg intraperitoneally. One week after diabetes induction, a 21-day treatment period was initiated. This involved administering propolis by gavage. Biological pa-rameters such as weight evolution, blood glucose levels, water consumption, as well as bio-chemical parameters (ALAT/ASAT), were measured throughout the experiment, and additional analyses were performed after sacrifice. Diabetic rats (D) showed a highly significant increase in blood glucose levels compared to the control rats (T). However, an improvement in blood glucose levels was observed in diabetic rats treated with propolis at doses of 150 mg/kg and 300 mg/kg during and after the treatment. The studied biochemical parameters (ALAT, ASAT) also revealed significant differences bet-ween diabetic rats and control rats. Additionally, diabetic rats treated with propolis showed a significant decrease in these parameters compared to untreated diabetic rats. This study indicates that propolis has superior anti-diabetic effects under current experimental conditions.
Keywords: diabètes; propolis; glycemia; rats; ASAT; ALAT